2000
DOI: 10.1103/physrevb.61.16084
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of gold nanoclusters on graphite

Abstract: We present a detailed molecular-dynamics study of the diffusion and coalescence of large (249-atom) gold clusters on graphite surfaces. The diffusivity of monoclusters is found to be comparable to that for single adatoms. Likewise, and even more important, cluster dimers are also found to diffuse at a rate which is comparable to that for adatoms and monoclusters. As a consequence, large islands formed by cluster aggregation are also expected to be mobile. Using kinetic Monte Carlo simulations, and assuming a p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
123
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(134 citation statements)
references
References 36 publications
10
123
1
Order By: Relevance
“…33 In Refs. [12][13][14] it was found that small nanoparticles (with up to several hundreds atoms) are very mobile in the temperature range 300-900 K and diffuse easily on a graphite surface. Moreover, in Ref.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…33 In Refs. [12][13][14] it was found that small nanoparticles (with up to several hundreds atoms) are very mobile in the temperature range 300-900 K and diffuse easily on a graphite surface. Moreover, in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…28 Therefore, our approach is a good starting point which should provide a qualitatively correct but not quantitatively precise description of the system which should be relevant for metal nanoparticles that weekly bind with graphene. 13 The simulation code is implemented using NVIDIA CUDA TM platform 30,31 which allowed us to carry out the computations on a single graphics processing unit (GPU) NVIDIA GeForce TM GTX 260. Algorithms for GPU based on the neighbor-list technique from Ref.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…26,45 Furthermore, surface diffusion on a substrate can occur thermally 46 and due to electrochemically 47,48 induced migration. This process is thus reasonably consistent with the TEM data and electrochemical measurements.…”
Section: = × 1 3 (3)mentioning
confidence: 99%
“…They have also been shown to relieve stress in strained films, greatly affecting the growth mode [2][3][4], and have been predicted [5,6] but never experimentally implicated in thermally activated surface diffusion of atom clusters. Instead, experimental studies of island diffusion have been mostly limited to homoepitaxial systems where island motion is a result of atomic diffusion events at steps [7][8][9][10][11], with collective cluster motion being negligible for groups of atoms of more than a few, with rare exceptions [12][13][14]. This work is at the confluence of bulk and surface phenomena by demonstrating that dislocations allow the movement of clusters by reducing the barrier for motion in the same way that they reduce the yield stress of bulk materials: by enabling slip to occur in a piecewise fashion.…”
mentioning
confidence: 99%